ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI RETENSI KARYAWAN DI PT SHARP ELECTRONIC INDONESIA - Ari Awaludin; Uus Mohammad Darul Fadli (JOURNAL SAINS STUDENT RESEARCH, 2024)
Elements of the work environment at PT Sharp Electronics Indonesia can contribute significantly to employee retention. A conducive, inclusive, and supportive work environment can increase job satisfaction and employee loyalty. This research will use a descriptive qualitative approach, collecting data through observation, interviews, and documentation studies. The results of the study are expected to provide a deeper understanding of Employee Retention at PT Sharp Electronic Indonesia. The results showed that employee retention at PT Sharp Electronic Indonesia tends to lead to employee retention to retain existing employees. This employee retention is needed by the company in order to make employees survive and have loyalty to the company and team. PT Sharp Electronics Indonesia, as a leading electronics company in Indonesia, faces challenges in retaining quality employees amidst intense industry competition. Elements of the work environment at PT Sharp Electronics Indonesia can contribute significantly to employee retention. A conducive, inclusive, and supportive work environment can increase job satisfaction and employee loyalty. This research will use a descriptive qualitative approach, collecting data through observation, interviews, and documentation studies. The results of the study are expected to provide a deeper understanding of Employee Retention at PT Sharp Electronic Indonesia. The results showed that employee retention at PT Sharp Electronic Indonesia tends to lead to employee retention to retain existing employees. This employee retention is needed by the company in order to make employees survive and have loyalty to the company and team. PT Sharp Electronics Indonesia, as a leading electronics company in Indonesia, faces challenges in retaining quality employees amidst intense industry competition.